Comparison of Criminal Law Related to the Trafficking of Human Body Organs in Indonesia and the Philippines - Restu Adhie Charisma; Aji Lukman Ibrahim (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
The purpose of the research in this paper is to analyze the actions that can be taken to prevent and eradicate the sale and purchase of human organs in Indonesia and to compare the enforcement of legal provisions on the trade in human organs in Indonesia and the Philippines. This scientific article uses normative legal research or library legal research, namely research conducted by examining library materials or secondary data, and the type of research in this writing is normative juridical research, which is studied with a statutory approach, meaning that a problem will be seen from the legal aspect by reviewing the laws and regulations. The results of the study show that the law in Indonesia still needs to be completed to find solutions for people who need organs and for donors with good ethics, regulations must be made. An important conclusion from this study is in the formation of laws to tackle and take action against trafficking in organs. It's good, but comparative studies from other countries are needed to make better laws and regulations.